Investigation of sediment avalanche phenomena - Zhao, Kuifeng. (2009)
Both upper and lower angles of repose in avalanching are investigated. The quantity of avalanching is obtained from experimental results. To identify the critical rotating speed for the rolling regime, the angles of repose, avalanche duration and avalanche cycle were studied. It is proposed that when the curves for the upper and lower angle of repose intersect with each other, rolling regime is reached. Besides, the quantity of avalanche is defined and the results are plotted versus rotating speed; the angles that the drum rotated during avalanche were also plotted; and the trend of the two plots show they tend to intersect at the particular rotating speed that upper and lower angle of repose intersect. A maximum wedge for avalanche is found and this could be particularly useful in mixing of particles. The wedge analysis is proved to be describing the quantity of avalanche excellently through the analysis of sound signal and the results of trajectory analysis. Avalanche duration is then investigated both theoretically and experimentally. A modified version of theoretical equation for avalanche duration fits experimental results better. Intersection of avalanche period and avalanche duration is another possible approach to identify the critical rotating speed for rolling regime. The upper and lower angles of repose are used in the simulation of scour hole fluctuation. For scour hole fluctuation, the dune properties are analyzed using MatLAB programming and the fluctuation of scour depth is then plotted. The properties of dunes are obtained from empirical equations, and then MatLAB programming is used to simulate the relationship between scour depth fluctuation and dune movement. Similarities and differences between scour fluctuation and rotating drum are briefly explained. Preliminary results show high frequency of avalanches implies more sand flows into the scour hole, and thus scour depth decreases; and scour depth increases otherwise.